Proceedings of the 5th Joint SIGHUM Workshop on Computational Linguistics for Cultural Heritage, Social Sciences, Humanities An 2021
DOI: 10.18653/v1/2021.latechclfl-1.8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Classification in German Plays with Transformer-based Language Models Pretrained on Historical and Contemporary Language

Abstract: We present results of a project on emotion classification on historical German plays of Enlightenment, Storm and Stress, and German Classicism. We have developed a hierarchical annotation scheme consisting of 13 subemotions like suffering, love and joy that sum up to 6 main and 2 polarity classes (positive/negative). We have conducted textual annotations on 11 German plays and have acquired over 13,000 emotion annotations by two annotators per play. We have evaluated multiple traditional machine learning appro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Drus and Khalid's (2019) study undertaken between 2014 and 2019, found that Naïve Bayes and Support Vector Machine (SVM) learning models were frequently used to detect polarity from text documents on sentiment analysis using a machine learning approach. Schmidt & Burghardt (2018), pointed out that sentiment analysis and emotion analysis are often performed using supervised Machine Learning (ML) or lexicon-based approaches. Supervised machine-learning algorithms are used as classifiers with a set of labelled data in order to classify the incoming words or phrases to appropriate sentiment or emotion categories.…”
Section: Sentiment and Emotion Analysismentioning
confidence: 99%
“…Drus and Khalid's (2019) study undertaken between 2014 and 2019, found that Naïve Bayes and Support Vector Machine (SVM) learning models were frequently used to detect polarity from text documents on sentiment analysis using a machine learning approach. Schmidt & Burghardt (2018), pointed out that sentiment analysis and emotion analysis are often performed using supervised Machine Learning (ML) or lexicon-based approaches. Supervised machine-learning algorithms are used as classifiers with a set of labelled data in order to classify the incoming words or phrases to appropriate sentiment or emotion categories.…”
Section: Sentiment and Emotion Analysismentioning
confidence: 99%